2017
DOI: 10.2196/jmir.7457
|View full text |Cite
|
Sign up to set email alerts
|

What Matters in Weight Loss? An In-Depth Analysis of Self-Monitoring

Abstract: BackgroundUsing technology to self-monitor body weight, dietary intake, and physical activity is a common practice used by consumers and health companies to increase awareness of current and desired behaviors in weight loss. Understanding how to best use the information gathered by these relatively new methods needs to be further explored.ObjectiveThe purpose of this study was to analyze the contribution of self-monitoring to weight loss in participants in a 6-month commercial weight-loss intervention administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 45 publications
4
64
0
2
Order By: Relevance
“…Food log feedback is directly dependent upon the participant’s engagement in providing food logs for an expert coach to review. Females received a greater amount of feedback due to logging a higher number of food logs than males, which has been reported in earlier studies [ 20 ]. However, this finding is linked to the understanding that personalized feedback increases engagement and weight loss outcomes [ 22 - 24 ].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Food log feedback is directly dependent upon the participant’s engagement in providing food logs for an expert coach to review. Females received a greater amount of feedback due to logging a higher number of food logs than males, which has been reported in earlier studies [ 20 ]. However, this finding is linked to the understanding that personalized feedback increases engagement and weight loss outcomes [ 22 - 24 ].…”
Section: Discussionsupporting
confidence: 69%
“…Although consistent self-monitoring is shown to have a predictive value for weight loss, the challenge is maintaining consistency among participants [ 20 ]. Findings support previous studies that personalized feedback and communication from expert coaches can produce greater engagement in self-monitoring activities when compared with tech-based interventions for self-monitoring without expert feedback [ 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have evaluated the use of eHealth technologies (e.g., websites, smartphone applications, text messages) to deliver WLM interventions. Furthermore, most research in this area has looked at short-term interventions (<6 months) without longer-term follow-up [ 8 , 9 ]. The small number of longer-term studies have reported a gradual regain of weight lost following treatment, with regain occurring after the first six months [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%